A bulk control circuit for open-loop front-ends for x-ray pixel detectors - Grande, Andrea; Fischer, Peter (IEEE transactions on nuclear science, 2017)
In this paper, we present a bulk control circuit to correct the chip-to-chip process variations of an open-loop nonlinear front-end (FE) for X-ray pixel detectors. Our study was carried out in the framework of the Depfet sensor with signal compression detector development for the European X-ray free electron laser. The presented circuit is capable to stabilize the FE response in presence of threshold voltage variations, acting on the bulk voltages of the FE's transistors and exploiting the body effect. The control circuit does not affect the noise performances of the FE. The working principle of the proposed control circuit and the first experimental results obtained with a first prototype realized in the 130-nm IBM technology are presented in this work.
Gesehen am 30.04.2018